2011
DOI: 10.1007/s00340-011-4453-z
|View full text |Cite
|
Sign up to set email alerts
|

Integration of fluorescence collection optics with a microfabricated surface electrode ion trap

Abstract: We have successfully demonstrated an integrated optical system for collecting the fluorescence from a trapped ion. The system, consisting of an array of transmissive, dielectric micro-optics and an optical fiber array, has been intimately incorporated into the ion-trapping chip without negatively impacting trapping performance. Epoxies, vacuum feedthrough, and optical component materials were carefully chosen so that they did not degrade the vacuum environment, and we have demonstrated light detection as well … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 15 publications
(14 reference statements)
1
45
0
Order By: Relevance
“…As a solution, dielectric mirrors are either placed far away from the trap [6][7][8][9][10] or the dielectric components are well shielded. 16,25,26,57,58 Therefore, when integrating a FFPC into an ion trap, the following restrictions should be respected: the ion-trap potential should be as deep as possible, and the trap geometry should be such that it shields the ion from any charges on the fibers. Furthermore, exposure of the fibers to UV light should be minimized in order to keep them from accumulating charges.…”
Section: A Experimental Design Considerationsmentioning
confidence: 99%
“…As a solution, dielectric mirrors are either placed far away from the trap [6][7][8][9][10] or the dielectric components are well shielded. 16,25,26,57,58 Therefore, when integrating a FFPC into an ion trap, the following restrictions should be respected: the ion-trap potential should be as deep as possible, and the trap geometry should be such that it shields the ion from any charges on the fibers. Furthermore, exposure of the fibers to UV light should be minimized in order to keep them from accumulating charges.…”
Section: A Experimental Design Considerationsmentioning
confidence: 99%
“…Van Devender et al [86] were first to demonstrate an embedded optical fiber; they collected fluorescence from an ion trapped above the surface through an integrated multi-mode fiber. Brady et al [95] created an ion trap chip incorporating an array of optical fibers and confirmed ion trapping and preliminary light detection with their system, establishing a proof of concept for a large fiber array trap architecture. Following this work on light collection, Kim et al [45] demonstrated light delivery through an integrated single-mode (SM) fiber.…”
Section: Laser Delivery Via Integrated Optical Fibermentioning
confidence: 91%
“…In particular, it can be shown that the equilibrium solution of (23), u(τ ) = 0, is stable if and only if the zero vector u 0 = 0, is stable under successive applications of U(T ) [5,6]. 3 If there is a vector v such that [U(T )] m v for m = 1, 2, . .…”
Section: Periodic Systems and Stabilitymentioning
confidence: 99%
“…[1][2][3] Since the electrodes all lie in a single plane, these traps can be constructed using VLSI microfabrication, which offers great scalability and potential to be integrated with other useful on-chip components such as mirrors, fiber ferrules, and cavities. The ions trapped by a surface trap are cooled by laser beams that are commonly aligned parallel to the trap surface.…”
Section: Introductionmentioning
confidence: 99%